2011
DOI: 10.1292/jvms.10-0470
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Simple Method to Obtain Canine Peripheral Blood-Derived Macrophages

Abstract: ABSTRACT. Macrophages play an important role in a variety of situations, including pathogen elimination, inflammation, and tissue repair. However, these cells are not fully studied in dogs, in part, due to the difficulty of efficiently isolating and culturing them in vitro. In this study, we cultured canine peripheral blood mononuclear cells (PBMCs) with 10 ng/ml of phorbol 12-myristate-13-acetate (PMA) for 5 days to obtain macrophages. A high number of round-adherent cells were obtained without the addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In our study, canine MDMs were negative for MHCII in both the control and ATRA-treated samples. Canine MDMs have been either positive [ 30 ], or nearly negative [ 31 ], for MHCII in previous reports, with expression likely depending on differentiation conditions that varied between studies. Our differentiation conditions were similar to those reported by Hartley et al [ 25 ], although their MDM phenotype was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, canine MDMs were negative for MHCII in both the control and ATRA-treated samples. Canine MDMs have been either positive [ 30 ], or nearly negative [ 31 ], for MHCII in previous reports, with expression likely depending on differentiation conditions that varied between studies. Our differentiation conditions were similar to those reported by Hartley et al [ 25 ], although their MDM phenotype was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes from peripheral blood were isolated as previously described for canine monocytes [ 28 ] with some modifications. Briefly, the gradient centrifugation steps occurred at 450× g without break at deceleration and the subsequent washes to remove platelets were performed at 200× g for a total of three washes.…”
Section: Methodsmentioning
confidence: 99%
“…PBMCs were incubated overnight at 37°C in a culture medium (RPMI-1640, Wako, Tokyo, Japan) to isolate the lymphocytes as floating cells. The adhered cells were collected as monocytes [12]. Total mRNA was extracted from lymphocytes and monocytes using a commercially available kit (RNAspin Mini RNA Isolation Kit; GE Healthcare, Buckinghamshire, England), according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%